Long Suffering Type 1 Diabetes Mellitus During Metabolic Acidosis on Positiveness of Ketones in Urine Patients - Mahayani, I Gusti Ayu Putu Sachita; Urip, Urip; Khusuma, Ari; Pauzi, Iswari (THRIVE Health Science Journal, 2024)
Examination of ketones in the patient's urine and measuring the patient's blood sugar level will determine whether there will be metabolic acidosis in patients with type 1 diabetes mellitus, which is a metabolic disorder that can be caused by various etiologies, such as chronic hyperglycemia due to impaired insulin secretion or impaired insulin action. alone. Diabetes Mellitus type 1 itself is more caused by reduced insulin secretion due to damage to pancreatic -cells. This study was conducted to examine ketones in urine on the duration of suffering from type 1 diabetes mellitus when metabolic acidosis occurs Data collection in this study was carried out by accidental sampling method by researchers to collect secondary and primary data on urine ketones in patients with metabolic acidosis. Based on research that has been done, data obtained from 34 patients with type 1 diabetes mellitus at the Sigerongan Health Center, as many as 8 patients with positive results of urine ketones with a prevalence of +2 totaling 3 people and +3 totaling 5 people. Judging from the high level of glucose (hyperglycemia) that is > 200 mg/dl and the positivity of ketone bodies in the patient's urine as a sign of metabolic acidosis. With a long-susceptibility to suffer from diabetes mellitus 1-5 years and above. The results of measuring ketone levels in the patient's urine show that there is no relationship with the duration of suffering from diabetes mellitus in the urine but blood sugar levels.